Perceptions and interpretations of benign situations: a study of organisational conflict using a dual-task method. (2015) - Workman, Michael
Organisational conflicts have been the topic of much study. However, even with this research and literature, as well as institutionalised human resource policies outlining professionalism and proper employee conduct, team-building activities, negotiation training, retreats, workshops, and conflict resolution interventions - conflicts continue to be an intransigent source of organisational dysfunction and failures. We developed a dual task test to investigate personality constructs, perceptions of others, and climate of incivility on conflicts. We found that certain personality characteristics led to more negative perceptions of benign situations and higher perceptions of incivility. Moreover, negative perceptions of benign situations and high perceptions of incivility led to more frequent organisational conflicts.